The antihypertensive effect of remote ischemic conditioning in spontaneously hypertensive rats - Li, Xiaohua; Ren, Changhong; Li, Sijie; Zhao, Wenbo; Wang, Peifu; Ji, Xunming (Frontiers in Immunology, 2023)
Purpose: Limb remote ischemic conditioning (LRIC) may be an effective method to control hypertension. This study investigated whether LRIC decreases blood pressure by regulating the hypertensive inflammatory response in spontaneously hypertensive rat (SHR). Method: The SHR and aged-matched Wistar rats with different ages were randomly assigned to the SHR group, SHR+LRIC group, Wistar group, and Wistar + LRIC group. LRIC was conducted by tightening a tourniquet around the upper thigh and releasing it for three cycles daily (10 mins x3 cycles). Blood pressure, the percentage of monocytes and T lymphocytes, and the concentration of pro-inflammatory cytokines in the blood were analyzed. Results: LRIC decreased blood pressure in SHR with different ages (4, 8, and 16 weeks old). Flow cytometry analysis showed that blood monocytes and CD8 T cells of SHR were higher than those of Wistar rats. LRIC significantly decreased the percentage of monocytes and CD8 T cells in SHR. Consistent with the changes of immune cells, the levels of plasma IL-6 and TNF-αin SHR were also higher. In addition, LRIC attenuated the plasma IL-6 and TNF-α levels in SHR. Conclusion: LRIC may decreased the blood pressure via modulation of the inflammatory response in SHR.